Advertising slogans in brand recall: Utterance analysis versus self-reporting - Pestana, M.H.; Wang, Wa; Moutinho, L. (Biometrics and neuroscience research in business and management: Advances and applications, 2024)
Purpose: To contribute to a more effective creation and management of slogans, testing how slogans variety and emotions conveyed by slogans influences consumers’ willingness to recall a brand. Design/methodology/approach: A focus group setting was established to select appropriate brands and products for the study. Data were gathered from a Self-Reporting questionnaire (SR) and from Voice Emotion Response (VER). All hypotheses were tested using Optimal Data Analysis, logistic regression; odds ratios and Kendal’s Tau b. Findings: Emotions, the antiquity of a brand and brand name have a positive relationship with brand recall, whereas a negative relationship is found with the length of slogans and the involvement presumed. Gender moderates the recall of brands and products, with men preferring brands having slogans with more extreme ratings of arousal, and women preferring slogans that are more spontaneous and sensitive. Research limitations/implications: Other results could be obtained using nonfamiliar brands. Practical implications: VER allows an immediate response to the consumer’s affective states, enabling practitioners to enhance the quality of their relationships. Managers should consider the long-term brand positioning, the likeability of the brands and how to build memorable slogans as crucial elements of brand positioning. Originality: The use of two techniques for register respondent’s emotions and the effect of some characteristics of slogans, brands and products on brand recall, gives a new and comprehensive approach to companies monitoring individual’s recall for products and brands for an effective advertising.